Organisational Gender Pay Gaps in the UK: What Happened Post-transparency? - Melanie K. Jones; Ezgi Kaya (Institute of Labor Economics (IZA), 2022)
Since April 2017 UK employers with over 250 employees have been required to publicly report their gender pay gap each year. We exploit this recent source of panel data on employer-level gender pay gaps to provide new insights for the established literature on the gender pay gap based predominately on employee information. More specifically, we explore the factors associated with changing organisational gender pay gaps in the period immediately following transparency. Consistent with information, reflection and pressure brought by the legislation, we find greater narrowing of gender pay gaps in organisations with a larger initial gender pay gap. Moreover, this relationship is magnified over time, consistent with gradual and longer-term adjustment. We further find evidence that interorganisational comparisons matter. For organisations with higher gender pay gaps than the average of their intra-industry comparators, lower comparator gender pay gaps are associated with further narrowing, suggesting relative comparisons enabled by transparency per se provide a channel through which the impact of the legislation operates.
Keywords: J31; J38; J78; 330; gender pay gap; pay transparency; equality legislation